Scaling the Graft Length and Graft Density of Irradiation‐Grafted Copolymers. Issue 21 (5th November 2018) - Nagy, Gergely; Sproll, Véronique; Gasser, Urs; Schmidt, Thomas J.; Gubler, Lorenz; Balog, Sandor
Abstract : Front Cover : In article1800311, Sandor Balog and co‐workers give experimental evidence—obtained via small‐angle scattering—demonstrating that the graft length and the graft density of radiation grafted copolymers may be scaled, and consequently, the dimensions and density of the phase‐segregated domains may be designed at wish in the future.